2007
DOI: 10.1016/j.marenvres.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of chemical tracers in assessing the diet and foraging regions of eastern North Pacific killer whales

Abstract: Top predators in the marine environment integrate chemical signals acquired from their prey that reflect both the species consumed and the regions from which the prey were taken. These chemical tracers-stable isotope ratios of carbon and nitrogen; persistent organic pollutant (POP) concentrations, patterns and ratios; and fatty acid profiles-were measured in blubber biopsy samples from North Pacific killer whales (Orcinus orca) (n = 84) and were used to provide further insight into their diet, particularly for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
120
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 36 publications
(61 reference statements)
14
120
3
1
Order By: Relevance
“…Ecotypes may also exhibit differences in social structure, morphology, behavior and vocal signatures (see for review de Bruyn et al (2013)). In the North Pacific, the resident and transient ecotypes occupy largely sympatric distribution ranges (Ford et al, 2000), but specialize on very different prey resources (fish and marine mammals, respectively; Ford et al, 1998;Krahn et al, 2007), are genetically differentiated (Hoelzel et al, 1998(Hoelzel et al, , 2002(Hoelzel et al, , 2007, and exhibit different social organization (Ford et al, 2000), mating systems (Pilot et al, 2010) and vocal behavior (Yurk et al, 2002;Deecke et al, 2005). Less is known about the 'offshore' ecotype, however, our data indicate that we need to consider their differentiation in sympatry as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecotypes may also exhibit differences in social structure, morphology, behavior and vocal signatures (see for review de Bruyn et al (2013)). In the North Pacific, the resident and transient ecotypes occupy largely sympatric distribution ranges (Ford et al, 2000), but specialize on very different prey resources (fish and marine mammals, respectively; Ford et al, 1998;Krahn et al, 2007), are genetically differentiated (Hoelzel et al, 1998(Hoelzel et al, , 2002(Hoelzel et al, , 2007, and exhibit different social organization (Ford et al, 2000), mating systems (Pilot et al, 2010) and vocal behavior (Yurk et al, 2002;Deecke et al, 2005). Less is known about the 'offshore' ecotype, however, our data indicate that we need to consider their differentiation in sympatry as well.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the 'offshore' ecotype, however, our data indicate that we need to consider their differentiation in sympatry as well. Krahn et al (2007) and Dahlheim et al (2008) found that 'offshore' killer whales feed on fish resources (possibly with some overlap with residents including halibut-Jones, 2006-but also distinct prey; Krahn et al, 2007), and sighting data indicate a largely but not exclusively pelagic distribution, (likely overlapping with both 'transient' and 'resident' ecotypes in some regions; Dahlheim et al, 2008), whereas the residents are more dependent on coastal resources. The average group size is larger and adult body size smaller for offshores than for either residents or transients, but data are based on just 59 sightings over 30 years (Dahlheim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, PBDE levels should continue to be monitored, because these compounds remain largely unregulated in the United States and Canada. Polybrominated diphenyl ethers have been reported in blubber biopsies taken from resident killer whales in the Gulf of Alaska and Aleutian Islands, demonstrating that these contaminants are present in the environment and accumulating at detectable concentrations at higher trophic levels [37]. The comparison between humpbacks from southern and northern California revealed significantly higher contamination in the south for all POP classes, even with a low sample size (n ¼ 5 for both regions).…”
Section: Geographic Variation Of Pops In Humpback Whalesmentioning
confidence: 96%
“…This approach has been used previously to understand population structure in harbor porpoise [40,41] as well as feeding regions for eastern North Pacific killer whales [37]. Identification of whales by feeding area could assist in …”
Section: Geographic Variation Of Pops In Humpback Whalesmentioning
confidence: 99%
“…However, organochlorine (OC) contaminants are less frequently used for dietary reconstruction, but they can allow for segregation of cetacean stocks (Borrell et al, 2006;Herman et al, 2005;Krahn et al, 2007;Pierce et al, 2008). OC accumulates through the food web and increases with the species trophic level (Hoekstra et al, 2003;Marsili and Focardi, 1996b;Ross et al, 2000;Weijs et al, 2009).…”
mentioning
confidence: 99%